(untitled) (International Journal of Food and Nutritional Sciences, 2023)
We need energy to heat our houses, cook our meals, travel, communicate with one another, power our companies, and carry out a variety of other growth activities; the need for energy throughout the globe is growing at an alarming rate. Solar power is quickly becoming one of the most promising forms of alternative energy for the 21st century. The use and storage of solar energy using indigo carmine- ascorbic acid- sodium lauryl sulphate photogalvanic cells is the focus of this research project. The purpose of the photogalvanic cell, as detailed in the current study effort, is to build a suitable photogalvanic energy device that can simultaneously be used for the production of solar power and the storage of that power. Additionally, optimal cell conditions were shown to exist for the viability of photogalvanic cells. At 10.4 milliwatts per square centimetre, the efficiency of solar energy conversion, fill factor, power storage capacity (t1/2), power at power point (Pp), photopotential (Voc), and equilibrium current (Isc) were observed to be on the order of 1.27 percent, 0.2269, 140 minutes, 132.27 milliwatts, 894 millivolts, and 724 micro ampere, respectively.